Prevalence of Glucose-6-phosphate dehydrogenase (G6PD) deficiency of newborns in Rasol Akram and Ali Asghar hospitals of Tehran - Ali Kazemi; Hossein Norouzi; Mahmood Tohidi Moghaddam; Alireza Naderloo (Iranian South Medical Journal, 2013)
Background: Glucose 6- phosphate dehydrogenase (G6PD) deficiency is a genetic disorder and assessment of newborns with or without this deficiency is counted as one of the effective components in public health evaluation in different countries. So, this study was aimed to assess prevalence of G6PD deficiency in newborns in Tehran. Material and Methods: This cross- sectional study was done on 1226 newborns (585 male, 641 female) in Rasol Akram and Ali Asghar hospitals in 2009. G6PD screening was done by fluorescent spot test method and G6PD activity was determined by Beutler method. Indices of weight, age, bilirubin level, blood group, and coomb’s test and reticulocyte count were recorded for all neonates. Obtained results were assessed using SPSS program (version 16) and T student and Chi square tests and (P<0.05) was considered significant. Results: Of 1226 newborns, 27 newborns (2/2 %) (12 male, 15 female) were G6PD deficient which of 27 neonates, 19 neonates had hyperbilirubinaemia. G6PD activity was 11/4±1.1 (U/gHb) in normal newborns but in G6PD deficient newborns was 2.2±0.63 (U/gHb) which difference between them was significant. (P=0.027) The mean value of bilirubin was 7.7±0.11 (mg/dL) in normal neonates but in deficient was 13.1±1.1 (mg/dL) which was statistically higher than normal newborns (P =0.047). Of total newborns transfusion exchange was done for 22 newborns which 8 neonates (36.3 %) of them were G6PD deficient. Conclusion: With regard to prevalence of 2.2 % of G6PD deficiency, necessity of cord blood samples’ assessment and training the high risk mothers for prevention of hyperbilirubinaemia induced neurologic damage (kernicterus) are recommended.